Erpetogomphus molossus, a new species from Sonora, Mexico (Odonata: Anisoptera: Gomphidae) - Bailowitz, Richard; Danforth, Doug; Upson, Sandy (Zootaxa, 2013)
Erpetogomphus molossus is described from 3 male and 3 female specimens (holotype and allotype in collection of Instituto Biologico de la Universidad Nacional Autónoma de México) from the intermittent pine-oak woodland of the Yécora municipio in east-central Sonora, Mexico. Diagnostic features of the new species include the seemingly bulbous tip (in lateral view) and prominent baso-ventral process of the male cerci and the notched and denticled posteromesal corners of the female subgenital plate.